Severe nigrostriatal degeneration without clinical parkinsonism in patients with polymerase gamma mutations - Tzoulis, Charalampos; Tran, Gia Tuong; Schwarzlmüller, Thomas; Specht, Karsten; Haugarvoll, Kristoffer; Balafkan, Novin; Lilleng, Peer K.; Miletic, Hrvoje; Biermann, Martin; Bindoff, Laurence A. (Brain (London, England : 1878), 2013)
The role of mitochondria in the pathogenesis of neurodegeneration is an area of intense study. It is known that defects in proteins involved in mitochondrial quality control can cause Parkinson's disease, and there is increasing evidence linking mitochondrial dysfunction, and particularly mitochondrial DNA abnormalities, to neuronal loss in the substantia nigra. Mutations in the catalytic subunit of polymerase gamma are among the most common causes of mitochondrial disease and owing to its role in mitochondrial DNA homeostasis, polymerase gamma defects are often considered a paradigm for mitochondrial diseases generally. Yet, despite this, parkinsonism is uncommon with polymerase gamma defects. In this study, we investigated structural and functional changes in the substantia nigra of 11 patients with polymerase gamma encephalopathy. We characterized the mitochondrial DNA abnormalities and examined the respiratory chain in neurons of the substantia nigra. We also investigated nigrostriatal integrity and function using a combination of post-mortem and in vivo functional studies with dopamine transporter imaging and positron emission tomography. At the cellular level, dopaminergic nigral neurons of patients with polymerase gamma encephalopathy contained a significantly lower copy number of mitochondrial DNA (depletion) and higher levels of deletions than normal control subjects. A selective and progressive complex I deficiency was seen and this was associated with a severe and progressive loss of the dopaminergic neurons of the pars compacta. Dopamine transporter imaging and positron emission tomography showed that the degree of nigral neuronal loss and nigrostriatal depletion were severe and appeared greater even than that seen in idiopathic Parkinson's disease. Despite this, however, none of our patients showed any signs of parkinsonism. The additional presence of both thalamic and cerebellar dysfunction in our patients suggested that these may play a role in counteracting the effects of basal ganglia dysfunction and prevent the development of clinical parkinsonism.